Productivity rate mathematical model analysis and development of graphical user interface (GUI) for linear arrangement with serial action automated flow line - Wong, Yok Shan (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This research is to design a PALSAS for productivity rate in a linear arrangement serial action automated flow line. Productivity is an important criterion for a manufacturing industry, so a method to measure, analysis, forecast and improvement are very important. When calculating for the productivity rate, it also needs a modle to caculate its result, but recenly most of the research has been using the current mathematical modle to calculate for it.